ASSOCIATION OF GENDER WITH ABO AND RH BLOOD GROUPS - A CROSS-SECTIONAL STUDY - Abbasi, Sana Qanber; Sattar, Rabia; Mansoor, Ghazal (Pakistan Journal of Physiology, 2018)
Background: Both the blood group types ABO and Rh are inherited in Mendelian fashion and are important from transfusion point of view. The objective of this study was to make the gender-based comparison of frequency of ABO and Rh blood groups among the medical and dental students of Sharif Medical and Dental College, Lahore. Methods: This cross-sectional study was conducted from Sep 2015 to Sep 2017. Blood groups of 514 students was determined by conventional methods and data was analysed with SPSS for gender differences. Results: A total of 514 students were included in the study. Out of 514 students, 186 (36.18%) were males and 328 (63.18%) were females. Out of the males 170 (91.4%), and out of females 301 (91.8%) were Rh positive. The prevalence of Rh negative group in male subjects was 8.6%, and in female subjects it was 8.2%. The frequencies of A, B, O and AB blood groups in Rh positive males were 23.66%, 31.18%, 29.03% and 7.53% respectively, and among females, it was 19.82%, 39.63%, 21.34% and 10.98% respectively. In Rh negative males the frequencies of A, B, O and AB blood groups were 1.08%, 3.76%, 2.15% and 1.61% respectively, and among females these were 1.22%, 2.74%, 3.35% and 0.91% respectively. Frequency comparison of ABO and Rh blood groups across the two genders was not significant (p=0.17 and 0.88 respectively) Conclusion: No statistically significant association of gender was found with ABO and Rh blood groups.